1986
DOI: 10.1042/bj2330929
|View full text |Cite
|
Sign up to set email alerts
|

Binding of inositol trisphosphate by a liver microsomal fraction

Abstract: Accumulating evidence suggests that the increase in cytosolic Ca2+ induced by receptor agonists is mediated by inositol 1,4,5-trisphosphate, a product of phospholipase C-mediated breakdown of phosphatidylinositol 4,5-bisphosphate. The present study employs inositol tris[32P]phosphate to demonstrate a specific receptor binding site in a microsomal fraction of rat liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

1987
1987
1996
1996

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(37 citation statements)
references
References 24 publications
1
35
0
1
Order By: Relevance
“…5 fig/ml of heparin. Spat and co-workers [14] have shown that the rate of dissociation of [32P]Ins (1,4,5)P3 from rat liver microsomal binding sites occurs monoexponentially, with a half-time of approx. 5.9-4.7 min at 4°C.…”
Section: Resultsmentioning
confidence: 99%
“…5 fig/ml of heparin. Spat and co-workers [14] have shown that the rate of dissociation of [32P]Ins (1,4,5)P3 from rat liver microsomal binding sites occurs monoexponentially, with a half-time of approx. 5.9-4.7 min at 4°C.…”
Section: Resultsmentioning
confidence: 99%
“…These results provide strong support for the hypothesis that InsP3 is a second messenger for releasing Ca2 + from the sarcoplasmic reticulum of vascular smooth muscle. In order to explain the Ca2+ release by InsP3, the existence of an InsP3 receptor on the intracellular stores has been proposed (Spat et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…One product of the hydrolysis, Ins(1,4,5)P3 (hereafter InsP3) is a modulator of Ca2+ levels within the cell (for reviews see [1,2]). InsP3 releases intracellular Ca2+ after binding to specific intracellular membrane-associated receptors, which have been identified in a wide variety of tissues [3][4][5][6][7][8][9][10][11]. Recently this receptor was purified to homogeneity from brain tissue [12].…”
Section: Introductionmentioning
confidence: 99%
“…InsP3 kinase and InsP3 phosphatase InsP3 kinase was measured by incubating [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Binding to cytoplasmic or detergent-solubilized fractions was assayed by spun-column chromatography [12]. Separation of enzyme activity NaCl (final concn.…”
Section: Introductionmentioning
confidence: 99%